Purchasing Power Parity Revisit: A Comparison of Linear and Nonlinear Models - Baharumshah, Ahmad Zubaidi; Wooi, Hooy Chee (Universiti Putra Malaysia Press, 2006)
This paper aims to expand PPP literature by twofold. First, the performance of the conventional linear PPP model (OLS) is compared with nonlinear PPP (GARCH). Secondly, we revisit the PPP by using more recent data for the currencies of five leading members of the Association of Southeast Asia ations (ASEAN-5), covering from January 1980 to ovember 2002, including the recent Asian financial crisis. Our results suggest that generally, the ASEAN-5 currencies still revert to their PPP equilibrium over long run time horizon. While all series show response to the crisis, the Philippine peso and Singapore dollar obviously received the least impact. Although Malaysia and Thailand have suffered huge undervaluation during the crisis, both Malaysian ringgit and Thai baht are found to be corrected at a quicker pace relative to the other three currencies from the misalignments. In addition, we also documented several nonlinear behaviors of the ASEAN-5 currencies and found that the nonlinear models outperform the linear model in modeling PPP, based on their superiority in out-of-sample forecasting.